“Infodemic” in time of COVID-19 - Mohamed, Shafizan (2020)
The world is in the middle of a health crisis matched only by historical pandemics like the flu, cholera and the plague that killed so many people. Needless to say, the COVID-19 pandemic we are facing today is a serious threat.